2013
DOI: 10.3109/19401736.2012.748041
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding common non-native freshwater fish species in Turkey: Low genetic diversity but high population structuring

Abstract: Negative impacts of introduced non-native freshwater species on native species have been increasingly recognized in the world as well as in Turkey. However, there has been relatively little attention on genetic characterization of alien freshwater fishes in their non-native distribution range and virtually no study has been conducted in Turkey despite its crucial importance in invasion biology. The purpose of this study was to elucidate genetic diversity of common non-native freshwater fish species (Carassius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…; Keskin et al. ; Loh et al. ) and is regularly used for a variety of applications, such as fishery management, biodiversity assessments and conservation (Triantafyllidis et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Keskin et al. ; Loh et al. ) and is regularly used for a variety of applications, such as fishery management, biodiversity assessments and conservation (Triantafyllidis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sequences for the same species are generally considered to be correctly identified when they form a monophyletic cluster on a neighbor-joining (NJ) tree with intraspecific distances that are below a given threshold (Srivathsan and Meier 2012). At present, this approach has proven to be highly efficient and reliable in many fish groups (Ward et al 2005;Hubert et al 2008Hubert et al , 2010Rock et al 2008;Keskin et al 2013;Loh et al 2014) and is regularly used for a variety of applications, such as fishery management, biodiversity assessments and conservation (Triantafyllidis et al 2011;Weigt et al 2012;Keskin et al 2013;Loh et al 2014;Shen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent large-scale assessments of diverse ichthyofauna confirmed that the use of the cytochrome oxidase I gene successfully capture a large portion of the alpha diversity for well-known fauna (April, Mayden, Hanner, & Bernatchez, 2011;Hubert, Hanner, & Holm, 2008a;Ward, Zemlak, Innes, Last, & Hebert, 2005a) but also helped in highlighting unrecognized (i.e., cryptic) diversity (Durand, Hubert, Shen, & Borsa, 2017;Hubert, Meyer, & Bruggemann, 2012;Jaafar, Taylor, Mohd Nor, Bruyn, & Carvalho, 2012;Pereira, Pazian, Hanner, Foresti, & Oliveira, 2011;Rock, Costa, & Walker, 2008;Winterbottom, Hanner, Burridge, & Zur, 2014). Landscape features such as fragmentation, however, proved to be a challenge to accurately delimit species through DNA barcodes (Geiger, Herder, & Monaghan, 2014;Keskin, Agdamar, & Tarkan, 2013;Knebelsberger, Dunz, Neumann, & Geiger, 2015). In the context of the YR ichthyofauna, a preliminary assessment of the effectiveness of DNA barcoding in identifying YR freshwater fishes confirmed its potential for conservation purposes (Shen, Guan, Wang, & Gan, 2016b;Shen, Kang, Chen, & He, 2016a).…”
mentioning
confidence: 99%
“…Therefore, the use of DNA barcodes as an accurate and effective method of species identi cation is currently favored by an increasing number of researchers. Recent studies have indicated that this technology is highly reliable and e cient in many sh groups, including freshwater shes (Keskin et al 2013) Moreover, it is widely used in a variety of elds, such as biodiversity assessment, sh larva identi cation and shery management (Gao 2015;Panprommin et al 2020).…”
Section: Introductionmentioning
confidence: 99%